he »other«, »different« & »them« - the expression of otherness and diferentness in Slovene and German phraseology - Fabčič, Melanija Larisa (Anali PAZU HD, 2022)
The perception of differentness, otherness and strangeness in a certain language community is often verbalized in form of phraseological units. The phraseology of a certain language is especially suitable for forming ideas about one´s own (national, cultural) identity and its opposite, the otherness. Identity is expressed as a s.c. autostereotype, the perception of the other and different as a non-experiential connotative heterostereotype. The article focuses on German and Slovene phraseological units, that contain an ethnonym and verbalize s.c. ethnic stereotypes: stereotypical opinions, positions and prejudices, that one language community has of another. The methods of cognitive linguistics (specifically prototypical models like the cognitive metaphore and conceptual integration) in combination with a socio-psychological aspect have proven particularly useful in analysis of phraseological units. At the center of the analysis are phraseological units with negative connotation and the question, to which ethnical groups do the Slovene and German phraseology attribute negative qualities.